Genetic profile of HIV-1 in the Republic Sakha, Yakutia - V. O. Kotova; O. E. Trotsenko; L. A. Balakhontseva; E. A. Bazykina; L. S. Sokolova; V. N. Kulagina; R. N. Fedorova; В. О. Котова; О. Е. Троценко; Л. А. Балахонцева; Е. А. Базыкина; Л. С. Соколова; et al. (Baltic Medical Education Center, 2023)
Aim. To perform molecular-genetic analysis of HIV-1 variants circulation in the Republic Sakha (Yakutia) and analysis of drug resistance mutations.Materials and methods. 123 patients diagnosed with HIV infection were examined. Mutations of drug resistance were detected via sequencing of amplified fragments of pol gene that is coding protease and a part of reverse transcriptase of HIV-1 using «Amplisens® HIV-Resist-Seq» test-system. Phylogenetic analysis was performed with software MEGA version 7.0.Results and discussion. Sub-subtype A6 that is prevalent in the Russian Federation was revealed most frequently (78.0%) in the examined group. Subtype B was detected in four cases (3.3%). Isolated cases of infection due to subtypes C, G and subsubtype A7 were revealed. Recombinant forms of the virus were found in 16.2% of the patients (n=20). Drug resistance mutations were revealed in 65 patients (52.8%) that were undergoing antiretroviral therapy (ART) which dictates a necessity of changing ART drugs.Conclusion. The results of the research state changes in the genetic profile of HIV-1 variants that were circulating during the last years in the Republic Sakha (Yakutia). Цель. Проведение молекулярно-генетического анализа вариантов ВИЧ-1, циркулирующих на территории Республики Саха (Якутия), включая анализ мутаций лекарственной устойчивости. Материалы и методы. Обследованы 123 пациента с диагнозом «ВИЧ-инфекция». Мутации резистентности выявляли методом секвенирования амплифицированных фрагментов гена pol, кодирующих протеазу и часть обратной транскриптазы ВИЧ-1, с использованием тест-системы «АмплиСенс® HIV-Resist-Seq». Филогенетический анализ выполняли с помощью программы MEGA версии 7.0. Результаты и их обсуждение. В обследованной группе преобладал характерный для России суб-субтип A6 (78,0%), в 4 случаях был обнаружен субтип В (3,3%), зафиксированы единичные случаи инфицирования субтипами С, G и субсубтипом А7. В 16,2% случаев (n=20) были обнаружены рекомбинантные формы вируса. Мутации лекарственной устойчивости ...